Reference values of auditory brainstem responses - Sotelo Muñoz, Milagros (2026)
Objective: To determine reference values of auditory brainstem responses (ABR) in individuals with normal hearing. Methods: A descriptive, non-experimental, cross-sectional study was conducted in 50 volunteer workers (33 women and 17 men) aged between 18 and 40 years, with normal hearing, from a national pediatric referral center in Lima, Peru. ABR recordings were obtained using a Nihon Kohden PV-230B device, employing click-type stimuli of 0.1 ms duration, rarefaction polarity, and intensities of 25, 40, 60, and 80 dB. Latencies of waves I, III, and V were analyzed, as well as the interpeak intervals I–III, III–V, and I–V. Results: The mean age was 31.46 ± 4.43 years. Latencies of waves I, III, and V progressively decreased as stimulus intensity increased from 25 to 80 dB. At 60 dB, the mean latencies were 1.89 ± 0.21 ms (wave I), 4.02 ± 0.25 ms (wave III), and 5.89 ± 0.31 ms (wave V) in the left ear, with very similar values in the right ear. The interpeak intervals at this intensity were 2.12 ± 0.23 ms (I–III), 1.87 ± 0.25 ms (III–V), and 4.00 ± 0.30 ms (I–V). At 80 dB, latencies decreased to 1.49 ± 0.09 ms, 3.66 ± 0.16 ms, and 5.59 ± 0.26 ms, respectively, with interpeak intervals of 2.17 ± 0.14, 1.92 ± 0.23, and 4.09 ± 0.24 ms. Differences between ears were minimal, and women showed shorter latencies in all waves, particularly in waves III and V. Conclusions: Reference values for ABR were established at the national pediatric referral center for individuals with normal hearing. Latencies and interpeak intervals showed high symmetry between ears, and slight sex-related differences were observed, with lower values in women.